Strategi Rebranding Citra Koperasi Melalui Instagram @kemenkopukm - Anggita Lestari Pangestuti Purnomo; Vina Mahdalena; Vinta Sevilla (Jurnal Ilmu Komunikasi, 2022)
This study aims to find out how the strategy of public relations officers of the State Ministry for Cooperatives and Small and Medium Enterprises (SMEs) in rebranding cooperatives through Instagram @kemenkopukm in order to change the negative citra of society about cooperatives. A qualitative method with a case study approach is applied in this research. The results of the study show that the Public Relations of the Ministry of Cooperatives and SMEs rebrand with a content marketing of social media strategy as follows, 1). Setting goals to change the negative citra of society by holding modern cooperatives. 2). Mapping the target market and determining the target audience in accordance with the goals. 3). Content planning, making editorial plans and looking for strategic issues that will be displayed on social media content. 4). Content creation, conducting material research, then the material is written by a script writer. 5). Ensure the content distribution regarding cooperative rebranding content can be easily accessed by the audience. 6). Doing collaboration with several related parties, coordinating with the Cooperative Supervision Task Force, Bareskrim, Attorney General, Financial Services Authority, and the Coordinating Minister for Political, Legal and Security Affairs. 7). Content repetition and evaluation of content marketing to measure whether the targeted goals is relevant with the plan.